Development and stability assessment of liquid paediatric formulations containing sildenafil citrate - Fátima Roque; Ana Cristina Rama; João José Sousa; Maria Eugénia Pina (Universidade de São Paulo, 2013)
The purpose of this study is to develop and improve oral liquids formulations of sildenafil citrate for paediatric use. Four different formulations were developed, which are as follows: two aqueous solutions of sildenafil citrate (2.5 mg/mL), with or without preservatives, and two other solutions of sildenafil in simple syrup (1.25 mg/mL), with or without preservatives. All of the formulations were physically, chemically and microbiologically stable for three months. The results of the stability studies allowed for the optimisation of formulations without preservatives due to their simplicity and their similar stable conditions when compared to the formulations containing antimicrobials. The shelf life of both formulations was three months; however, upon opening, aqueous solutions should be used within 10 days and kept refrigerated, and syrup solutions should be used within 14 days in a hospital setting.